Integrasi Digital-Based PjBL-STEM untuk Meningkatkan Keterampilan Proses Sains pada Siswa SMP - Sutanto Sutanto; Mohammad Masykuri; Sukarmin Sukarmin (Universitas Sebelas Maret, 2025)
Education is essentially an activity carried out by students producing changes in themselves. STEM-based learning(Science, Technology, Engineering, and Mathematics) can train students to apply their knowledge and improvescience process skills in learning using digital technology. Learning model recommended for use in the MerdekaCurriculum is a student-centred learning model, one of which is the Project Based Learning (PjBL). This study willanalyse the influence of STEM education integrated with a digital-based PjBL model on improving students' scienceprocess skills. This research uses the meta-analysis method. Research data were obtained from national andinternational journals. The meta-analysis study is based on indicators of science process skills. Based on secondarydata review, it shows that the integration of PjBL with digital-based STEM can be maximally implemented if theteacher is directly involved in learning, where the teacher acts as an inspirer, motivator, and facilitator. The learningstages of integrating PjBL with digital-based STEM starting from the design process to presenting the results canimprove students' science process skills. The integration of PjBL with digital-based STEM must be well prepared,starting from the use of learning strategies must be well designed and the dimensions of the assessment must becarefully selected so that the use of multidisciplinary learning is expected to be well realized in secondary education.